OsLAP3/OsSTRL2, encoding a rice strictosidine synthase, is required for anther cuticle formation and pollen exine patterning in rice - Chen, Dai-bo; Zhou, Ran; Wang, Hui-min; Zhang, Pei-pei; Yang, Zheng-fu; Xuan, Dan-dan; Zhang, Ying-xin; Zhan, Xiao-deng; Cao, Li-yong; Cheng, Shi-hua; Sun, Lian-ping (Frontiers in Plant Science, 2025)
The formation of the anther wall and the development of pollen processes, central to rice fertility and yield, are highly dependent on the synthesis and accumulation of lipid polymers. Although several regulatory factors related to lipid biosynthesis during pollen wall development have been identified, the molecular mechanisms controlling these processes remain poorly understood. In this study, a male-sterile rice mutant, lap3, was identified, characterized by normal vegetative growth but complete male sterility due to delayed programmed cell death (PCD) in tapetal cells and defects in anther cuticle and pollen exine formation. Map-based cloning revealed that OsLAP3 is a new allele of the strictosidine synthase-like gene, OsSTRL2. Functional analysis, including complementation and CRISPR/Cas9-based gene editing, confirmed that the 2-nucleotide deletion in the OsLAP3 is responsible for the male sterility phenotype. OsLAP3 is homologous to the maize ZmMS45, the core recessive nuclear sterile gene of maize Seed Production Technology (SPT), and localizes to the endoplasmic reticulum and plays a conserved role in anther development and pollenformation. Gene expression analysis revealed a significant downregulation of key genes involved in anther development and sporopollenin biosynthesis in lap3 anthers. Furthermore, lipid profiling demonstrated a marked reduction in both wax and cutin content. These findings establish OsLAP3 as a critical regulator of fatty acid synthesis and highlight its role in anther cuticle formation and pollen exine development. The findings of this study provide valuable insights into the molecular regulation of lipid biosynthesis during rice male reproductive development and offer potential applications for hybrid rice breeding.